Comparative study on FFE activities between Korean and Japanese NPD projects. (3rd December 2014) - Nagahira, Akio; Kim, Kyong–Hwan; Yoon, Hee–Ja; Ishihara, Sumie; Chiba, Yukiya; Tanaka, Yuta; Miura, Aya
The aim of this study was to focus on the fuzzy front end (FFE) activities of both Korean and Japanese manufacturers' new product development (NPD) projects, and to reveal the characteristics of key FFE factors for NPD success between them. We analysed 293 NPD projects in Korean manufacturing firms and 540 NPD projects in Japanese manufacturing firms using structural equation modelling (SEM). The results suggest Korean manufacturing companies were focusing much more on the reduction of market uncertainty than the reduction of technical uncertainty when they developed new products, in order to perform highly in such areas as sales volume, profit, and market share. On the other hand, since Japanese manufacturing companies paid attention to both the efficiency and effectiveness of NPD project success when they developed new products, they expended much more energy on R&D and labour. A common crucial key to project success was 'intensity of planning' before the start of development.